Patient-centered palliative care in pediatric cardiology: a cardiophenomenological approach - M. D. Miroshnichenko; D. I. Nozdrachev (Российский кардиологический журнал)
Despite the success of pediatric cardiology and cardiac surgery in the treatment of severe heart diseases in children, a significant increase in the average life expectancy and quality of life of patients, cardiovascular diseases remain common reasons leading to the need for palliative care. A number of psychological and ethical aspects in pediatric palliative care in cardiology are not sufficiently developed. Cardiac diseases requiring palliative care affect the physiological, psychological and social aspects of patients' lives, and require special attention. It is proposed to use the second-person methods in clinical communication based on the biopsychosocial approach of cardiophenomenology in order to provide a patient-centered environment in palliative care for children with severe heart diseases. Cardiophenomenology can provide non-paternalistic relationships in palliative care for pediatric patients with cardiovascular disease to improve health-related quality of life (HRQoL).